Negotiated settlements in bribery cases a principled approach - (Abiola). (Cheltenham, UK Northampton, MA, USA Edward Elgar Publishing Limited, 2020)
Achieving effective enforcement in cases of complex, multi-layered, multi-jurisdictional acts of bribery that occur in utmost secrecy is a challenging area of corporate crime enforcement. This thought-provoking book examines the scope, benefits and challenges of negotiated settlements - a form of non-trial enforcement - as a mechanism, and demonstrates the need for a more harmonized and principled approach to deterring corporate bribery. Written by a global team of experts with backgrounds in legal practice, policy work and academia, this timely book offers a truly international perspective, considering negotiated settlements in view of a variety of different legal systems and traditions. Drawing on recent empirical research, the contributors' analyses of these settlements in the context of fundamental criminal law principles offer unique insight and functional solutions to the difficult problem of holding corporations liable for crime. - The book's deep reflection on criminal law principles will be beneficial for scholars and students of economic crime, corruption and criminal law. Equally, its contributions to a policy area undergoing rapid development will be invaluable for policymakers, enforcement practitioners and government officials"--
Introduction Abiola Makinwa and Tina Søreide -- Part I Context -- Negotiated settlements in a broader law enforcement context Mark Pieth -- The path of FCPA [Foreign Corrupt Practices Act] settlements Brandon L. Garrett -- Public/private cooperation in anti-bribery enforcement : non-trial resolutions as a solution? Abiola Makinwa -- The implications of negotiated settlements for debarment in public procurement : a preliminary enquiry Sope Williams-Elegbe -- Settlements within the World Bank Group Sanctions system Pascale Hélène Dubois, Kathleen M. Peters and Roberta Berzero -- Part II Deterrence -- Prosecutors discretionary authority in efficient law enforcement systems Tina Søreide and Kasper Vagle -- The potential promise and perils of introducing deferred prosecution agreements outside the U.S. Jennifer Arlen -- Incentives for self-reporting and cooperation Lucinda A. Low and Brittany Prelogar -- The DOJs anti-piling on policy : time to reflect? Sharon Oded -- Part III Justice -- What counts as a good settlement? Kevin E. Davis -- Corporate compliance and privatization of law enforcement : a study of the Italian legislation in light of the U.S. experience Simone Lonati and Leonardo S. Borlini -- Justice for whom? : the need for a principled approach to deferred prosecution agreements in England and Wales Susan Hawley, Colin King and Nicholas Lord.
Includes bibliographical references and index.
Keywords: Meditation. -- Electronic book; Law reform; Comromise (Law); Briery -- Law and legislation